STUDENTS’ PERCEPTIONS OF STRUCTURE AND WRITTEN EXPRESSIONS COMPREHENSION IN TOEFL - Ratnaningsih, Paskalina Widiastuti (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2022)
English test is needed to measure students’ comprehension on the material. There are several types of English tests. One of English tests for international use is TOEFL. TOEFL is used by many individuals to measure their abilities of English. This study would like to analyze students’ perceptions of Structure and Written Expression skills that are difficult and moderate to be learned. This study used survey research. It was conducted in a university where the sample was semester 7 students. This study used questionnaire as the instrument. The result showed that most of the respondents understood the material. However, several skills which were conjunctions, connectors, present and past participles, adjective and adverb, adjective after linking verbs were mostly difficult to be learned.